2022
DOI: 10.1038/s42003-022-03761-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual PET-fMRI reveals a link between neuroinflammation, amyloid binding and compensatory task-related brain activity in Alzheimer’s disease

Abstract: The interplay among neuropathological mechanisms underlying Alzheimer’s disease (AD), as neuroinflammation and amyloid-beta (Aβ), as well their impact on neuronal function remains elusive. A major gap in knowledge is the functional impact of neuroinflammation. The posterior cingulate cortex (PCC), as the most prominent site of amyloid pathology in AD, is a pivotal region to investigate the concomitant presence of pathophysiological mechanisms such as microglia activation, indexing neuroinflammation, and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, some studies have shown reduced posterior cingulate gyrus/precuneus activation and hyperactivation in frontal regions, including the precentral gyrus, in MCI patients in comparison to CN individuals during memory tasks (Hampstead et al ., 2011 ; Jin et al ., 2012 ; Terry et al ., 2015 ). In AD, MTL hypoactivation, reduced posterior cingulate gyrus/praecuneus deactivation and frontal hyperactivation are approximately consistent findings during memory tasks (Canário et al ., 2022 ; Jonin et al ., 2022 ; Parra et al ., 2013 ; Petrella et al ., 2007 ; Pihlajamäki and Sperling, 2009 ; Yetkin et al ., 2006 ).…”
Section: Mrimentioning
confidence: 99%
“…Furthermore, some studies have shown reduced posterior cingulate gyrus/precuneus activation and hyperactivation in frontal regions, including the precentral gyrus, in MCI patients in comparison to CN individuals during memory tasks (Hampstead et al ., 2011 ; Jin et al ., 2012 ; Terry et al ., 2015 ). In AD, MTL hypoactivation, reduced posterior cingulate gyrus/praecuneus deactivation and frontal hyperactivation are approximately consistent findings during memory tasks (Canário et al ., 2022 ; Jonin et al ., 2022 ; Parra et al ., 2013 ; Petrella et al ., 2007 ; Pihlajamäki and Sperling, 2009 ; Yetkin et al ., 2006 ).…”
Section: Mrimentioning
confidence: 99%
“…The early detection of AD is of paramount importance for effective patient management and prognostication. PET tracers for glucose metabolism [8,[22][23][24], amyloid [25,26], tau [27][28][29][30][31][32], and neuroinflammation imaging [33][34][35][36][37][38][39], as well as MRI techniques such as arterial spin labeling (ASL) [40][41][42], resting-state fMRI and task-related fMRI [43][44][45][46][47][48][49][50][51][52], multi-nuclear MRI [53,54], and chemical exchange saturation transfer (CEST) [55,56], have provided valuable insights into the pathological mechanisms of AD in patients (Table 1). Synapse loss is a major pathological change in AD, but its relationship to functional and structural connectivity dysfunction remains unclear.…”
Section: Pet/mr Imaging In Admentioning
confidence: 99%